(untitled) (Reflection and Critique Law Magazine, 2020)
This article aims to address the principle of human rights and popular sovereignty in the terms in which they were studied by Jürgen Habermas. Alluded to the philosopher developed the study on this theme with the aim of applying his theory of rational discourse as a stabilizer of the tension existing between the two principles. In this sense, it is intended, through this article, to analyze the tension between the idea of ​​human rights and popular sovereignty. Therefore, initially, it is necessary to deal with both themes from the perspective of thinkers Jean-Jacques Rousseau and Immanuel Kant. A posteriori, it is the critical analysis developed by Habermas about the referred perspectives, in order to elucidate the existing tension. In Habermas’ view, only an understanding of the internal nexus between human rights and popular sovereignty will make it possible to achieve cohesion in the implementation of public policies.